2005
DOI: 10.1038/sj.ejhg.5201389
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine levels – before and after methionine loading – in 51 Dutch families

Abstract: Elevated levels of homocysteine are a risk factor for vascular disease, thrombosis, neural tube defects and dementia. The 677C4T polymorphism in the methylenetetrahydrofolate reductase (MTHFR) gene appears to be the most important single determinant of plasma homocysteine concentration. In the current study, we estimated heritability and fit a series of models of inheritance for both fasting and postmethionine-load homocysteine levels in the HOFAM-study (HOmocysteine in FAMilies study), which included 306 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…However, we did not observe a similar relationship in the presence of Hcy alone (50 μM). Our observation is in line with Den Heijer's et al study, which showed that the postload homocysteine levels had stronger genetic determination than the fasting homocysteine levels [23]. In addition, current data suggests that MP number may be genetically regulated [12].…”
Section: Discussionsupporting
confidence: 92%
“…However, we did not observe a similar relationship in the presence of Hcy alone (50 μM). Our observation is in line with Den Heijer's et al study, which showed that the postload homocysteine levels had stronger genetic determination than the fasting homocysteine levels [23]. In addition, current data suggests that MP number may be genetically regulated [12].…”
Section: Discussionsupporting
confidence: 92%
“…12,29,30 Souto et al 29 found modest heritability for homocysteine levels (0.24) in 21 Spanish pedigrees ascertained on the basis of thrombophilia. Jee et al 12 found a heritability of 0.47 for homocysteine levels in 661 family members of 112 probands who underwent elective Chr indicates chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…The strong homocysteine-lowering effect of folate supplementation 46 indicates that this form of dysfunctional folate metabolism can be overcome by additional folate intake. Because homocysteine concentrations are to a large extent under genetic control 47,48 , homocysteine can be used as a biomarker to detect human NTD candidate genes that are involved in storage, transport and metabolism of folate. The identification of such genetic variants will also contribute to our understanding of the mechanisms underlying the role of folate in the prevention of NTDs.…”
Section: Genetic Variation In Folate Metabolismmentioning
confidence: 99%